Triggering preservice teachers’ writing skills through genre-based instructional model viewed from creativity - Haerazi Haerazi; Lalu Ari Irawan; Taufik Suadiyatno; Heri Hidyatullah (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study was aimed at finding out the effectiveness of genre-based instructional model in the teaching of writing skills viewed from students’ creativity. This study employed a quasi-experimental research design. The samples consisted of two classes in which one class was treated by using genre-based instructional (GBI) model and the second class was subjected to the process-based instruction (PBI) model. The writing test and creativity test were functioned as research instruments to collect the data in both classes. The data were analyzed by using the multifactor analysis of variance (ANOVA). The research finding informed that the GBI model was more effective than the PBI model. It was proved with the value of sig. (0.008) was lower than sig. level 0.05. Thus, students having high creativity have better writing achievement than those who have low creativity and it was proved with the value of sign (0.000) was lower than sig. level 0.05. It means that the effect of instructional model and writing skills rests on the level of students’ creativity. The finding indicates that there is significant interaction between instructional model being applied and creativity in the teaching of writing skills.